Dehydrated alfalfa to control intake of self-fed sows during gestation - Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials with 47 second-and third-litter sows and one trial involving 40 gilts were conducted to evaluate self-feeding a diet containing 96% dehydrated alfalfa during gestation. Sows were maintained in outside lots (approximately 2 1/2 acres) until the 100 - 110th day of gestation. The control gestation ration (15% protein sorghum-soybean meal) was fed in individual feeding stalls at 2 kg (4.4 lbs.) per head per day. All sows were fed a 16% protein diet ad libitum during the 28-day lactation period. Trial I using Yorkshire sows started in July with sows farrowing in September. Trial II using Duroc sows started in September with sows farrowing in November and December. Gilts bred in March and April and farrowing in June were used in trial III Intake of self-fed sows was measured weekly. In the first trial, feed intake of self-fed sows averaged 3.88 kg (8.54 lbs.) daily with a gestation weight gain of 29 kg (53.8 lbs.). Self-fed sows in trial II consumed an average of 2.90 kg (6.38 lbs.) daily and gained 23.3 kg (51.3 lbs.) during gestation. Self-fed gilts in trial III consumed an average of 2.56 kg (5.63 lbs.) daily and gained 19.6 kg (43.2 lbs.) from 30 days post-breeding to farrowing. Control gilts gained 39.1 kg (86.0 lbs.) during gestation.
Swine Day '76 is known as Swine Day, 1976
Keywords: Swine; Farrowing; Gestation; Lactation; Gilts